Design of a hybrid ANN multi-objective whale algorithm for suspended sediment load prediction - Ehteram M.; Ahmed A.N.; Latif S.D.; Huang Y.F.; Alizamir M.; Kisi O.; Mert C.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
accuracy assessment; algorithm; artificial neural network; design method; optimization; prediction; suspended sediment; Iran; algorithm; animal; Cetacea; Iran; Algorithms; Animals; Iran; Neural Networks, Computer; Whales